2018
DOI: 10.1021/acs.analchem.8b01622
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Induced Unfolding of Partially Metalated Metallothionein-2A: Tracking Unfolding Reactions of Gas-Phase Ions

Abstract: Metallothioneins (MTs) constitute a group of intrinsically disordered proteins that exhibit extreme diversity in structure, biological functionality, and metal ion specificity. Structures of coordinatively saturated metalated MTs have been extensively studied, but very limited structural information for the partially metalated MTs exists. Here, the conformational preferences from partial metalation of rabbit metallothionein-2A (MT) by Cd, Zn, and Ag are studied using nanoelectrospray ionization ion mobility ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 48 publications
5
49
0
1
Order By: Relevance
“…This recalls the offset collision-induced unfolding of proteins in presence of divalent cations. [45][46] To summarize, together with our previous study on DNA and RNA double helices, 11 our results…”
Section: Rna Hairpins and Kissing Complexes Are Significantly More Cosupporting
confidence: 64%
“…This recalls the offset collision-induced unfolding of proteins in presence of divalent cations. [45][46] To summarize, together with our previous study on DNA and RNA double helices, 11 our results…”
Section: Rna Hairpins and Kissing Complexes Are Significantly More Cosupporting
confidence: 64%
“…Recently, a paper reported collision-induced unfolding experiments followed through ion mobility-MS for Zn 4 MT2. 74 The authors reported four separate conformers with regard to collision cross section (CCS) profiles that required a different collision activation for unfolding. The β-domain is not fully extended but rather folded for Cd 4 MT2, as opposed to Zn 4 MT2, which showed a CCS of around 1000, which corresponds to the β-domain being fully extended.…”
Section: Resultsmentioning
confidence: 99%
“…However, this idea has been supported by neither Russell’s group nor here. 74 , 75 Russell’s group concluded that the region from Asn18 to Cys38 participates in the coordination of the first four Zn 2+ ions, but the terminal Cys5 or Cys7 are at most weakly interacting. Here, with the experimental conditions employed, we suggest that the region 21–30 participates in Zn 2+ binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen et al 105 e Ngu et al 106 investigaram metalotioneínas associadas ao Cu e Cd por ESI-MS, o uso de ICP-MS em combinação com a técnica de separação mostrou-se eficiente na análise de ferramentas das isoformas de MTs. 9,52 Dong et al 19 utilizando uma combinação de mobilidade iônica com nESI-MS, foram capazes de determinar diretamente as várias conformações que a população iônica pode apresentar, bem como as informações de tamanho de íons que podem estar relacionadas à estrutura e conformação.…”
Section: Espectrometria De Massaunclassified